“Invisible Deaths”: A Critical Analysis of the Study of Prison Homicide - Holt, Karen M. (Homicide studies, 2024)
Prison homicide, or homicides that occur between individuals who are incarcerated, has received a dearth of attention in scholarly literature. These homicides have increased over the past several decades with devastating consequences for those housed within prison walls, correctional and administrative staff, the families of those incarcerated, and the communities from which they are removed. Perpetrators of prison homicides often continue to engage in violence despite incapacitation, calling into question the ability of the state to house individuals safely. When fatal violence occurs, victims of these homicides are constructed as deserving of violence. Drawing from critical criminological perspectives of state-sanctioned violence, I argue that treatment of these victims affects the legitimacy of the criminal justice system and public safety.